Composite of single walled carbon nanotube and sulfosalicylic acid doped polyaniline: a thermoelectric material. (4th August 2016) - Chatterjee, Mukulika Jana; Banerjee, Dipali; Chatterjee, Krishanu
Abstract: Nanocomposites containing single walled carbon nanotubes (SWCNTs) and highly ordered polyaniline (PANI) have been synthesized employing an in situ polymerization using different weight percentages of single-walled carbon nanotube (SWCNT) as template and aniline as a reactant. The composites show homogeneously dispersed SWCNTs which are uniformly coated with PANI through a strong interface interaction. Structural characterization shows that the PANI cultivated along the surface of the SWCNTs in an ordered manner during the SWCNT-directed polymerization process. Measurements at room temperature displayed a significant enhancement in both the electrical conductivity and thermoelectric power which could be attributed to the more ordered chain structures of the PANI on SWCNT. As a result, the power factor of the composite is improved which increases with temperature. At the same time, the measured value of thermal conductivity at room temperature being lowest among the reported values, has resulted in best ZT at room temperature. The lowest value of thermal conductivity is attributed to the large phonon scattering due to the introduction of nanointerfaces.